1992
DOI: 10.1016/0741-5214(92)90009-w
|View full text |Cite
|
Sign up to set email alerts
|

Femoral pseudoaneurysm from drugs of abuse: Ligation or reconstruction?

Abstract: A plan for management of infected arterial pseudoaneurysm has evolved from our experience with 23 such aneurysms treated between 1981 and 1989 and followed for up to 66 months. Eighteen femoral artery aneurysms are the primary focus of this report. Because we were concerned about the high probability of amputation expected from acute interruption of the femoral artery, we were reluctant to limit initial management to ligation and debridement alone. However, significant complications developed in 12 patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 14 publications
1
73
0
2
Order By: Relevance
“…A mycotic aneurysm with abscess formation develops [1]. The abscess may not be pulsating [7,13]. The growing fibrous tissue often channels the spreading of the aneurysm into the retroperitoneal space.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A mycotic aneurysm with abscess formation develops [1]. The abscess may not be pulsating [7,13]. The growing fibrous tissue often channels the spreading of the aneurysm into the retroperitoneal space.…”
Section: Discussionmentioning
confidence: 99%
“…The growing fibrous tissue often channels the spreading of the aneurysm into the retroperitoneal space. In such cases attempted diagnostic aspirations will produce negative results [7]. In another case series of 50 patients, 17% were initially misdiagnosed as having either cellulitis or an abscess [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Padberg et al [26], in a study of 18 patients with infected femoral false aneurysms secondary to IVDA, reported on their aggressive use of limb revascularisation due to their concerns about high rates of limb loss when limiting their initial management to vessel ligation and debridement. Twelve of the 18 patients underwent revascularisation in the initial peri-operative period, resulting in 3 amputations and 13 secondary arterial operations in this re-vascularised group, in contrast to no amputations in those patients undergoing vessel ligation with no reconstruction [26]. Both Padberg and Arora et al [27], advocate a test clamp of the distal external iliac/proximal common femoral and assessing pedal doppler signals.…”
Section: Discussionmentioning
confidence: 99%